2005
DOI: 10.1021/es0497328
|View full text |Cite
|
Sign up to set email alerts
|

A Field Comparison of Volatile Organic Compound Measurements Using Passive Organic Vapor Monitors and Stainless Steel Canisters

Abstract: Concurrent field measurements of 10 volatile organic compounds (VOCs) were made using passive diffusion-based organic vapor monitors (OVMs) and the U.S. Federal Reference Method, which comprises active monitoring with stainless steel canisters (CANs). Measurements were obtained throughout a range of weather conditions, repeatedly over the course of three seasons, and at three different locations in the Minneapolis/St. Paul metropolitan area. Ambient concentrations of most VOCs as measured by both methods were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…To obtain stable P-values in weighted regression, the maximum number of estimable parameters is limited to the denominator degrees of freedom of the variance estimator (i.e., the number of primary sampling clusters minus the number of sampling strata) (Research Triangle Institute, 2001 Chung et al (1999), comparing passive samplers to canister whole-air samplers suggests negative bias for the passive samplers, but further states that differences are likely less than 25%. More recently, Pratt et al (2005) have conducted a comparison of passive samplers similar to those used in NHANES and canister whole-air samplers for VOCs and support the small bias conclusion of Chung et al (1999). Both of these studies involved laboratory and field components, but not personal monitoring.…”
Section: Strengths and Limitationssupporting
confidence: 62%
“…To obtain stable P-values in weighted regression, the maximum number of estimable parameters is limited to the denominator degrees of freedom of the variance estimator (i.e., the number of primary sampling clusters minus the number of sampling strata) (Research Triangle Institute, 2001 Chung et al (1999), comparing passive samplers to canister whole-air samplers suggests negative bias for the passive samplers, but further states that differences are likely less than 25%. More recently, Pratt et al (2005) have conducted a comparison of passive samplers similar to those used in NHANES and canister whole-air samplers for VOCs and support the small bias conclusion of Chung et al (1999). Both of these studies involved laboratory and field components, but not personal monitoring.…”
Section: Strengths and Limitationssupporting
confidence: 62%
“…Thus, in descending order of preference, OVMs were placed (1) in a covered porch area, (2) under the eaves of the house, and (3) in a covered carport area. This resulted in four eave locations, five (Chung, Morandi, Stock, & Afshar, 1999;Chung et al, 2004;Mukerjee et al, 2004;Pratt et al, 2005;Weisel et al, 2005) and has been used extensively elsewhere (Cohen et al, 1990;Ware et al, 1993;Sexton et al, 2004). Quantitative analysis for a target list of 31 VOCs was performed by means of solvent extraction of OVM charcoal badges followed by gas chromatography/mass spectrometry (GC/MS).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the compound sampled, organic vapor monitors have been reported to underestimate (Stock et al 1999) or overestimate (Pratt et al 2005) concentrations when compared to canisters. Dobos (2000) reported that styrene concentrations measured by organic vapor monitors were 31% higher than measurements from sorbent tubes.…”
Section: Implications Of Sampling Approachesmentioning
confidence: 99%